Comparative Performances of Natural Dyes Extracted from Mentha Leaves, Helianthus Annuus Leaves, and Fragaria Fruit for Dye-Sensitized Solar Cells - Abdulrahman Z.H.; Hachim D.M.; Al-murshedi A.S.N.; Kamil F.; Al-Manea A.; Yusaf T. (MDPI, 2023)
During the last four centuries, there have been extensive research activities looking for green and clean sources of energy instead of traditional (fossil) energy in order to reduce the accumulation of gases and environmental pollution. Natural dye-sensitized solar cells (DSSCs) are one of the most promising types of photovoltaic cells for generating clean energy at a low cost. In this study, DSSCs were collected and experimentally tested using four different dyes extracted from Mentha leaves, Helianthus annuus leaves, Fragaria, and a mixture of the above extracts in equal proportions as natural stimuli for TiO2 films. The result show that solar energy was successfully turned into electricity. Additionally, DSSCs based on mixtures of dyes showed better results than those based on single dyes. Efficiency (?) was 0.714%, and the fill factor (FF) was 83.3% for the cell area. 2022 by the authors.